Cardiomyocyte Proliferative Capacity Is Restricted in Mice With Lmna Mutation - Onoue, Kenji; Wakimoto, Hiroko; Jiang, Jiangming; Parfenov, Michael; DePalma, Steven; Conner, David; Gorham, Joshua; McKean, David; Seidman, Jonathan G.; Seidman, Christine E.; Saito, Yoshihiko (Frontiers in Cardiovascular Medicine, 2021)
LMNA is one of the leading causative genes of genetically inherited dilated cardiomyopathy (DCM). Unlike most DCM-causative genes, which encode sarcomeric or sarcomere-related proteins, LMNA encodes nuclear envelope proteins, lamin A and C, and does not directly associate with contractile function. However, a mutation in this gene could lead to the development of DCM. The molecular mechanism of how LMNA mutation contributes to DCM development remains largely unclear and yet to be elucidated. The objective of this study was to clarify the mechanism of developing DCM caused by LMNA mutation. Methods and Results: We assessed cardiomyocyte phenotypes and characteristics focusing on cell cycle activity in mice with Lmna mutation. Both cell number and cell size were reduced, cardiomyocytes were immature, and cell cycle activity was retarded in Lmna mutant mice at both 5 weeks and 2 years of age. RNA-sequencing and pathway analysis revealed “proliferation of cells” had the most substantial impact on Lmna mutant mice. Cdkn1a, which encodes the cell cycle regulating protein p21, was strongly upregulated in Lmna mutants, and upregulation of p21 was confirmed by Western blot and immunostaining. DNA damage, which is known to upregulate Cdkn1a, was more abundantly detected in Lmna mutant mice. To assess the proliferative capacity of cardiomyocytes, the apex of the neonate mouse heart was resected, and recovery from the insult was observed. A restricted cardiomyocyte proliferating capacity after resecting the apex of the heart was observed in Lmna mutant mice. Conclusions: Our results strongly suggest that loss of lamin function contributes to impaired cell proliferation through cell cycle defects. The inadequate inborn or responsive cell proliferation capacity plays an essential role in developing DCM with LMNA mutation.